2015
DOI: 10.2139/ssrn.2640096
|View full text |Cite
|
Sign up to set email alerts
|

On the Relation between Capital Flows and the Current Account

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The latest sub-group concerns non-euro area member states, 54 in order to compare our results for the euro area with countries with a di¤erent currency. The outcome appears to be very much in ‡uenced by the presence of CEE new member states in the sample.…”
Section: Other Sub-groups and Gdp Growth Resultsmentioning
confidence: 99%
“…The latest sub-group concerns non-euro area member states, 54 in order to compare our results for the euro area with countries with a di¤erent currency. The outcome appears to be very much in ‡uenced by the presence of CEE new member states in the sample.…”
Section: Other Sub-groups and Gdp Growth Resultsmentioning
confidence: 99%
“…1 2 We do have a dummy for the years after 2008, in order to control for a possible break after the beginning of the global crisis. 1 3 As in Oeking and Zwick (2015), the …nancial account Granger-causes the current account during economic upturns (data on OECD countries). More speci…cally, short-term ‡ows seem to …nance the current account during economic downturns, while inducing its changes during upturns.…”
Section: Misalignments and Data Description 31 Calculation Of The Misalignmentsmentioning
confidence: 99%
“…Other sub-groups and GDP growth results The latest sub-group concerns non-euro area member states, 54 in order to compare our results for the euro area with countries with a di¤erent currency. The outcome appears to be very much in ‡uenced by the presence of CEE new member states in the sample.…”
Section: Sub-groups Bayesian Panel Varmentioning
confidence: 99%
“…More recent research has also clearly indicated a causal relationship from capital account to financial account. Oeking and Zwick (2015) analyse the relationship between current account balance and capital movements for 23 selected OECD countries, examining quarterly data between 1990 and 2013 using the Granger causality test. The empirical results show that in the OECD countries current account developments generally determine movement in the financial account.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, determining the source of the increase in total demand is a crucial issue in identifying the direction of the causality relationship between capital and current account. One group of economists claims that foreign capital is required to finance a growing current account deficit based on expanding domestic demand, which results in changes in the financial account (Higgins and Klitgaard 1998;Lau and Fu 2011;Oeking and Zwick 2015;Urbanovsky 2017). Thus, any increase in domestic demand, whether from the private or the public sector, causes a deficit in the current account, whereupon foreign capital is needed to finance this deficit in the current account.…”
Section: Introductionmentioning
confidence: 99%